TINGKAT ADOPSI PETANI TERHADAP BUDIDAYA ALTERNATIF TANAMAN SAYURAN PADA MUSIM KEMARAU DI LAHAN RAWA LEBAK (Local Farmers Adoption to Alternative Vegetables Cultivation during Dry Season at Tropical Riparian Wetland) - Widuri, Laily Ilman; Siaga, Erna; Kartika, Kartika; Meihana, Mei; Lakitan, Benyamin (LPPM Universitas Bina Insan, 2020)
Generally, vegetables cultivation in tropical riparian wetland is conducted only one times per year simultaneously or after rice cultivation. One of constrains of cultivation in tropical riparian wetland is low adoption to technology which can be used by local farmers during dry season. The objective of this research was to introduce result of research to local farmer directly and examine the local farmer’s adoption about the technology based on research to apply in tropical riparian wetland, Pemulutan, South Sumatera. Based on this research, results showed that farmers' interest in cultivating vegetables during the dry season is still low, but it has a chance to be improved. Alternative solutions through watering and adjustment of environmental conditions or adaptation through the selection of cultivation locations and the selection of various types of vegetable crops have been carried out by farmers. However, the application of mulch has not been practiced by farmers in tropical riparian wetland for vegetable cultivation during the dry season due to limited information received, considered as capital intensive, and the sociocultural aspects of the local community.